THE ROLE OF BLACK TOURISM IN LOCAL DEVELOPMENT - THE OLD CITY OF MOSUL AS A MODEL - Naser Nazar Mohamed Raof (Scholar Express Journals, 2023)
Black tourism is one of the terms that has recently appeared in the academic field and refers to tourism that is associated with dark and inhuman events such as death, suffering and violence. And that was behind the conversion of battlefields, battles, and prisons, as well as the sites of tragedies, incinerators, massacres, and disasters, into tourist destinations, museums, and dark tourism factories, regardless of the motive for that, whether it was inclinations, curiosity, or passion
Keywords: Dark Side; Travel; Black tourism